2014
DOI: 10.1108/ilt-12-2011-0109
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the application of YAG laser texturing technology to the cylinder wall of auto engine

Abstract: Purpose -The purpose of this study was to develop a new approach using a pulse YAG laser with rational power density and pulse width to texture desired discrete distribution morphology on the cylinder wall. Design/methodology/approach -Variational rules of the effects of these three parameters were found by calculating the oil film on the cylinder/piston ring system. The experiment results were compared between laser texturing cylinders and conventional honing cylinders. Findings -It was found that the coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Koszela et al 15 conducted experimental investigations of the oil pockets distribution effects on the tribological performance under mixed lubrication conditions, validating surface texturing results in significant improvement in wear resistance. By texturing on cylinder liner with emphasis on dimple distribution angle, Yang et al 16 found laser texturing could improve the anti-wear property in comparison with mechanical honing. For different circumstances, Yu et al 17 suggested that the design of dimple patterns should follow the hydrodynamic principle.…”
Section: Introductionmentioning
confidence: 99%
“…Koszela et al 15 conducted experimental investigations of the oil pockets distribution effects on the tribological performance under mixed lubrication conditions, validating surface texturing results in significant improvement in wear resistance. By texturing on cylinder liner with emphasis on dimple distribution angle, Yang et al 16 found laser texturing could improve the anti-wear property in comparison with mechanical honing. For different circumstances, Yu et al 17 suggested that the design of dimple patterns should follow the hydrodynamic principle.…”
Section: Introductionmentioning
confidence: 99%
“…Textured dimples have the function of trapping wear debris. Researches by He et al (2015b), Zhan and Yang (2014), Borghi et al, (2008), Segu and Hwang (2015), Roy et al (2015), Hammouti et al (2015) showed that evacuation of wear particles out of contact was a crucial point to avoid abrasive wear caused by the presence of a third body. Wang et al, 2014 reported that hardened edges of laser dimples could further enhance wear resistance of textured specimens.…”
Section: Friction and Wear Propertiesmentioning
confidence: 99%
“…Circular dimple texture is commonly used because it is featured with processing convenience and easy implementation (Wakuda et al, 2003;Pettersson and Jacobson, 2006;Zhou et al, 2015). Zhan and Yang (2014) showed that friction coefficient and wear rate were reduced in laser dimple textured cylinders. He et al (2015b) reported that micro dimples on beryllium bronze specimen surfaces achieved using femtosecond laser had good wear resistance performance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, micro-dimples and nano-dimples are considered as the important surface texturing for improving the tribological properties of interacting surfaces in micro-electro-mechanical systems (Yasumaru et al, 2008). Most of the texturing is applied on the substrates, where laser is applied directly onto the metal surface (Zhan and Yang, 2014;Lin et al, 2015). Other surface improvement such as applying coating on coated metal is still in research progress.…”
Section: Surface Texturingmentioning
confidence: 99%